Effect of UV irradiation on apatite deposition on anodised TiO2 coating formed under mixed acid solution - Saleh Elfallah, Saleh Suliman; Mohamed Yunus, Mohd Radzi; Abdullah, Hasan Zuhudi (UR Publishers, 2018)
Anodic oxidation method is used to produce thick TiO2 coating layer in a mixture of acids electrolyte to modify the TiO2 which is naturally formed on Ti with only few nanometers thick and inert. The TiO2 coating is then underwent in vitro test to evaluate their bioactivity in simulation body fluid (SBF). In the present work, oxide coatings of TiO2 were formed on Ti-Cp foil under potentials of 150V at current density of 100 mA.cm-2 for 10 min. Multiple characterization techniques were used. X-ray diffraction (XRD) is used to obtain mineralogical phase. Scanning electron microscope (SEM) is used to obtain surface morphology. Chemical absorption of the apatite precipitation was tested by using Fourier transform infrared spectroscopy (FT-IR). Surface morphology from the results shows an increased porosity with smaller pore size for TiO2 formed in mixed acids with higher molar concentration. According to in vitro results it was concluded that apatite precipitation was higher on TiO2 coatings with increased Ti-Ofunctional groups formed using UV.